(untitled) (Estudios Sociales, 2020)
The work starts from a problem of several decades in the field of historians: their fear of the allegedly anti-contextualist proposals that emerge from the work of Jacques Derrida. The hypothesis is that in a non-caricatural reading of the famous formula «there is no outside the text» it shows that, far from denying the existence or importance of the context, the French author wants to suggest that the text cannot be isolated, because he is edgeless. Starting from wondering if the problem does not lie more in the way of conceiving the contextualization work, the famous «incriminated» passage and the way in which the suspicion that surrounds it began to circulate, and then examine the role of context in Derrida and end with a contextualization of Derrida himself and his work in light of the presence / absence of the unspeakable of historical trauma.